Impact of residue retention and nutrient management on carbon sequestration, soil biological properties, and yield in multi-ratoon sugarcane - Pradhan, Aliza; Wakchaure, Goraksha C.; Shid, Dhanashri; Minhas, Paramjit S.; Biswas, Ashis K.; Reddy, Kotha Sammi (Frontiers in Sustainable Food Systems, 2023)
Sequestration of carbon (C) in arable cropping systems is considered one of the potential climate change mitigation strategies. In this context, assessing the potential of sugarcane cropping systems should be a priority, as it leaves substantial amounts of recyclable residues essential for maintaining soil organic carbon (SOC), improving soil health, and strengthening overall resources. We evaluated the impacts of residue retention and nutrient management practices on SOC and its pools, storage, soil biology, and yield in a multi-ratooning sugarcane system. A field experiment was conducted in the split-plot design with residue burning (RB) and residue retention (RR) as the main plot treatments and three nutrient management practices, that is, 25% of the recommended dose of fertilizers (RDF, i.e., 300:150:150 kg of N, P2O5, and K2O kg ha−1, respectively) as basal + 75% through fertigation (N1); 50% of RDF as basal + 50% through fertigation (N2); and 75% of RDF as basal + 25% through fertigation (N3) as subplot treatments in ratoon sugarcane. Soil samples were collected initially and after 6 years of multi-ratooning (one plant and four ratoon crops) from a soil depth of 0–30 cm. The results indicated that RR plots had 21% higher total SOC with 42, 47, 17, and 13% higher very labile, labile, less labile, and non-labile C pools, respectively, than RB plots (P < 0.05). RR also had a higher lability and recalcitrant index than RB. Of the total SOC stock, the contribution of passive pools was higher (72–75%) than active pools. Significantly higher dehydrogenase activity (DHA) (86%), alkaline phosphatase activity (APA) (16%), and ß-glucosidase activity (BGA) (22%) were observed in RR plots as compared to RB plots, whereas for nutrient management practices, it followed the order of N2 > N3> N1. Microbial counts also followed the same trend as that of enzyme activities. Residue retention practices reported higher C sequestration (0.68 Mg C ha−1 yr−1), carbon retention efficiency (37%), and yield (38%) with a potential to reduce GHG emissions by 2.72 Mg CO2 ha−1 yr−1 as compared to traditional practices. Residue retention and 50–75% RDF as basal is recommended for higher soil C retention and soil biology for sustained sugarcane productivity.